The Use of Modality in the Texts Markobar in Pabagas Boru Ceremony as Mandailing Oral Tradition - Asrita Sari (Association of Language Teachers in Southeast Asia (ALTSA), 2025)
The research's goal was to find out why the markobar texts used the modality in the pabagas boru ritual. Qualitative research methodology was employed. In Padangsidimpuan, two Pabagas Boru (wedding) ceremonies provided the data. This research focused on the 14 markobar roles in the Pabagas Boru ritual and two atobangon (markobar experts) in Padangsidimpuan. As the research's data, there were 66 sentences with modality that participants provided orally. Halliday's (2004) modality theory was applied to examine the rationale for the usage of modality in the markobar texts during the Pabagas Boru ceremonies. The data were analyzed based on Miles, Huberman, and Saldana (2014). The results showed that there were four reasons of modality use, namely, (1) to portray possibilities that happened in a new family; (2) to express the speakers’ opinion and suggestion; (3) to obligate the new couple in creating a better family; and (4) to tell the speakers’ willingness toward the new couple.